Essays in the economics of knowledge : innovation, collaboration, and organizational complementarities - Leiponen, Aija (Acta Universitatis Oeconomicae Helsingiensis, 2000)
Tiivistelmä.
Keywords: innovaatiot; organisaatiot; osaaminen; innovationer; organisationer; kunnande